The Role of ATP in Sleep Regulation - Chikahisa, Sachiko; Séi, Hiroyoshi (Frontiers in Neurology, 2011)
One of the functions of sleep is to maintain energy balance in the brain. There are a variety of hypotheses related to how metabolic pathways interact with sleep/wake regulation. A major finding that demonstrates an interaction between sleep and metabolic homeostasis is the involvement of adenosine in sleep homeostasis. An accumulation of adenosine is supplied from ATP, which can act as an energy currency in the cell. Extracellularly, ATP can act as an activity-dependent signaling molecule, especially in regard to communication between neurons and glia, including astrocytes. Furthermore, the intracellular AMP/ATP ratio controls the activity of AMP-activated protein kinase (AMPK), which is a potent energy regulator and is recently reported to play a role in the regulation of sleep homeostasis. Brain ATP may support multiple functions in the regulation of the sleep/wake cycle and sleep homeostasis.